P59 Monitoring the recovery time of children after elective tonsillectomies using commercial activity trackers, an prospective feasibility study. Issue 6 (17th May 2019) - Lambrechtse, PIP; Ziesenitz, VC; Atkinson, A; Bos, EJ; Welzel, T; Gilgen, Y; Gürtler, N; Cohen, AF; Van Den Anker, JN
Abstract : Introduction: Wearable activity trackers are increasingly incorporated into daily life and are advancing in their technology in means of accuracy, validity and acceptability, 1-6 however there is deficient knowledge on using these devices in a paediatric setting. The objective of this pilot study was to assess the feasibility of physical activity tracking in children 7 before and after a standardized surgical intervention and to assess the recovery time after surgery. Methods: This was a single centre, open-label, prospective feasibility study. We aimed at recruiting 24 children and adolescents 4–16 years of age undergoing elective tonsillectomy. The preoperative period was 10 days before surgery and the postoperative period was 28 days. Activity data were gathered with activity trackers. 8 Reference activity was defined as the individual mean of daily steps preoperatively. Recovery time was defined as the number of days that the patient needed to reach reference activity postoperatively. The population was stratified according to age (4–7, 8–16 years). Results: Twelve male and twelve female patients participated (mean age 6yr, mean BMI percentile 44.7). The age group 4–7 years had a mean recovery time of 11.2 days (SD 5.0) compared to 8.3 days (SD 1.7) in the age group 8–16. The difference was 2.9 days. The tracker datasets were 58% complete. The rate of technical failures of the trackers was 29.2% for the total study period. Conclusions: Activity trackers are a potential tool viable to assess recovery time after surgery in children. Recovery time after tonsillectomy seems to be age-dependent with older children recovering faster. For future studies, we recommend using trackers as a part of assessing physical activity as a parameter of general wellbeing of child during or after an intervention. Using wearable activity trackers is a more modern and appropriate method to assess physical activity, 9-14 especially in a paediatric population. References: Brooke SM, An HS, Kang SK, Noble JM, Berg KE, Lee JM. Concurrent validity of wearable activity trackers under free-living conditions. J Strength Cond Res 2017;31(4). Fokkema T, Kooiman TJM, Krijnen WP, Van Der Schans CP, De Groot M. Reliability and validity of ten consumer activity trackers depend on walking speed. Med Sci Sports Exerc . 2017;49(4). Evenson KR, Goto MM, Furberg RD. Systematic review of the validity and reliability of consumer-wearable activity trackers. Vol. 12, International Journal of Behavioral Nutrition and Physical Activity 2015. Huang Y, Xu J, Yu B, Shull PB. Validity of FitBit, Jawbone UP, Nike+ and other wearable devices for level and stair walking. Gait Posture 2016; Hein IM, Troost PW, De Vries MC, Knibbe CAJ, Van Goudoever JB, Lindauer RJL. Why do children decide not to participate in clinical research: A quantitative and qualitative study. Pediatr Res 2015; Van Berge Henegouwen MTH, Van Driel HF, Kasteleijn-Nolst Trenité DGA. A patient diary as a tool to improve medicine compliance. Pharm World Sci 1999;21(1):21–4. Stone AA. Patient non-compliance with paper diaries. BMJ 2002; Disclosure(s): Nothing to disclose